2021
DOI: 10.1136/annrheumdis-2021-221048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of risankizumab for active psoriatic arthritis: 24-week results from the randomised, double-blind, phase 3 KEEPsAKE 2 trial

Abstract: ObjectivesRisankizumab is an interleukin-23 inhibitor under study for the treatment of patients with psoriatic arthritis (PsA). The phase 3 KEEPsAKE 2 trial investigated the efficacy and safety of risankizumab versus placebo in patients with active PsA who had previous inadequate response or intolerance to ≤2 biological therapies (Bio-IR) and/or ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD-IR). Results through week 24 are reported here.MethodsAdults with PsA who were Bio-IR and/or cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 35 publications
3
56
0
1
Order By: Relevance
“…The companion KEEPsAKE 2 trial (NCT03671148) is evaluating similar endpoints in a patient population that includes patients with a history of inadequate response or intolerance to biological agents. 5 The results of the initial 24-week double-blind period of the ongoing KEEPsAKE 1 study are reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…The companion KEEPsAKE 2 trial (NCT03671148) is evaluating similar endpoints in a patient population that includes patients with a history of inadequate response or intolerance to biological agents. 5 The results of the initial 24-week double-blind period of the ongoing KEEPsAKE 1 study are reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 444 patients with PsA were randomised to receive RZB (n=224) or PBO (n=220), and baseline characteristics were balanced between groups (table 1). One patient was randomised but did not receive the study drug and thus was excluded from the full analysis set population 14. As previously reported, 215 (96.0%) and 199 (90.5%) patients who received RZB or PBO, respectively, completed the week 24 study visit 14…”
Section: Resultsmentioning
confidence: 99%
“…KEEPsAKE 2 (NCT03671148) is a Phase 3, randomised, PBO-controlled, double-blind, multicentre study comparing the effects of RZB with PBO after 24 weeks of treatment in patients with active PsA who have an inadequate response or intolerance to one or two biologic disease-modifying antirheumatic drugs (DMARDs) (Bio-IR) and/or to ≥1 conventional synthetic DMARD (csDMARD-IR) 14. Patients were randomised 1:1 to receive RZB 150 mg or PBO by subcutaneous injection at weeks 0, 4 and 16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, IL-23 inhibitors include other agents initially used for psoriasis, such as guselkumab and risankizumab, that, following recent trials, showed efficacy and are now approved for adult PsA ( 71 75 ). Although few data are available for pediatric patients, this opens other future possibilities for juvenile psoriasis and JPsA.…”
Section: Treatmentmentioning
confidence: 99%